MALAT1: A Pivotal lncRNA in the Phenotypic Switch of Gastric Smooth Muscle Cells via the Targeting of the miR-449a/DLL1 Axis in Diabetic Gastroparesis - Wang, Yanjuan; Wang, Yan; Zhu, Boqian; Zhu, Ying; Jiang, Ya; Xiong, Wenjie; Lin, Lin; Gong, Yaoyao (Frontiers in Pharmacology, 2021)
Diabetic gastroparesis (DGP) is a common complication of diabetes mellitus (DM). Our previous study suggested that the expression of the long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is closely related to DGP. However, the role of MALAT1 in DGP pathogenesis remains unclear. Here, we aim to characterize the role of MALAT1 in DGP. First, we analyzed the lncRNA expression profiles through lncRNA sequencing. Next, we detected MALAT1 expression in the stomach tissues of DGP model mice and diabetic patients. Then, we investigated the role and mechanisms of MALAT1 in the proliferation, migration, phenotypic switch, and carbachol-induced intracellular Ca2+ changes in human gastric smooth muscle cells (HGSMCs) under high glucose (HG) conditions, using short hairpin RNA technology, RNA immunoprecipitation, and dual-luciferase reporter assays. We show that MALAT1 expression was upregulated in the gastric tissues of DGP model mice, the adjacent healthy tissues collected from diabetic gastric cancer patients with DGP symptoms, and in HGSMCs cultured under HG conditions. Functionally, MALAT1 knockdown in vitro impacted the viability, proliferation, migration and promoted the phenotypic switch of HGSMCs under HG conditions. Additionally, we show that MALAT1 sponged miR-449a, regulating Delta-like ligand 1 (DLL1) expression in HGSMCs; any disturbance of the MALAT1/miR-449a/DLL1 pathway affects the proliferation, migration, phenotypic switch, and carbachol-induced Ca2+ transient signals in HGSMCs under HG conditions. Collectively, our data highlight a novel regulatory signaling pathway, the MALAT1/miR-449a/DLL1 axis, in the context of DGP.